Persistent homology for time series and spatial data clustering. Issue 15 (September 2015) - Pereira, Cássio M.M.; de Mello, Rodrigo F.
Highlights: We explore computational topology for clustering. We focus on time series and spatial data. Shape features are extracted based on n -dimensional holes. We run experiments with synthetic and real-world data. Results show improvements when compared to traditional clustering. Abstract: Topology is the branch of mathematics that studies how objects relate to one another for their qualitative structural properties, such as connectivity and shape. In this paper, we present an approach for data clustering based on topological features computed over the persistence diagram, estimated using the theory of persistent homology. The features indicate topological properties such as Betti numbers, i.e., the number of n -dimensional holes in the discretized data space. The main contribution of our approach is enabling the clustering of time series that have similar recurrent behavior characterized by their attractors in phase space and spatial data that have similar scale-invariant spatial distributions, as traditional clustering techniques ignore that information as they rely on point-to-point dissimilarity measures such as Euclidean distance or elastic measures. We present experiments that confirm the usefulness of our approach with time series and spatial data applications in the fields of biology, medicine and ecology.